2020
DOI: 10.1080/15592294.2020.1737355
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hydroxymethylation ofANGPTL4is associated with selective intrauterine growth restriction in monochorionic twin pregnancies

Abstract: Selective intrauterine growth restriction (sIUGR) is a severe complication in monochorionic (MC) twin pregnancies, and it carries increased risks of poor prognosis. Current data suggest that vascular anastomoses and unequal placental sharing may be the key contributor to discordant foetal growth. While MC twins derive from a single zygote and have almost identical genetic information, the precise mechanisms remain unknown. DNA hydroxymethylation is a newly discovered epigenetic feature associated with gene reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In the analysis of other hypoxia-related factors in twin pregnancies, HIF1α expression was elevated in the placental sector of the smaller fetus in sFGR pregnancies [ 111 , 112 , 113 ], indicating the presence of more severe hypoxia than in an uncomplicated twin pregnancy. The results of aberrant hydroxymethylation of angiopoietin-like 4, a hypoxia-responsive gene regulated by HIF-1α, and increased expression of miR-199a, a master regulator of a hypoxia-triggered pathway targeting HIF-1α in the smaller placental sectors of sFGR, are consistent with the results noted above [ 114 , 115 ]. There is only one report noting evidence that HIF-1α was primarily observed in trophoblastic cells and villus capillary endothelial cells in the donor placenta from TTTS compared with that in the control placenta from non-TTTS twin pregnancies, but the expression of HIF-1α in the recipients tended to be similar to the controls [ 116 ].…”
Section: Hypoxia-related Factorssupporting
confidence: 89%
“…In the analysis of other hypoxia-related factors in twin pregnancies, HIF1α expression was elevated in the placental sector of the smaller fetus in sFGR pregnancies [ 111 , 112 , 113 ], indicating the presence of more severe hypoxia than in an uncomplicated twin pregnancy. The results of aberrant hydroxymethylation of angiopoietin-like 4, a hypoxia-responsive gene regulated by HIF-1α, and increased expression of miR-199a, a master regulator of a hypoxia-triggered pathway targeting HIF-1α in the smaller placental sectors of sFGR, are consistent with the results noted above [ 114 , 115 ]. There is only one report noting evidence that HIF-1α was primarily observed in trophoblastic cells and villus capillary endothelial cells in the donor placenta from TTTS compared with that in the control placenta from non-TTTS twin pregnancies, but the expression of HIF-1α in the recipients tended to be similar to the controls [ 116 ].…”
Section: Hypoxia-related Factorssupporting
confidence: 89%
“…The exact pathogenesis of sIUGR in twin pregnancy remains unknown, though uneven placental sharing and vascular anastomoses appear relevant [4][5][6]. Given that monochorionic twins have identical genetic information, the role of epigenetic factors warrants serious consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Selective intrauterine growth restriction (sIUGR) occurs in approximately 10%-15% of monochorionic twins and frequently causes perinatal morbidity and mortality [1,2]. The mechanisms underlying this disorder remain unclear because monochorionic twins originate from the same zygote and have identical genomes [3,4]. Considering the contribution of unequal placental sharing and vascular anastomoses to inconsistent fetal development [4][5][6], it is reasonable to speculate that the pathogenesis may be associated with the transportation of nutrients like amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in global DNA hydroxymethylation in selective intrauterine growth restriction (sIUGR) placentas was described in a study of MZ twins [ 48 ]. Similarly, Zhang and colleagues also observed a decrease in global 5hmC levels in the smaller placental share of sIUGR pregnancies [ 49 ]. Additionally, the authors observed lower levels of 5hmC in the promoters of ANGPTL4 and HIF1A genes, which are hypoxia-responsive genes that were downregulated in the smaller placental share of sIUGR [ 49 ].…”
Section: Dna Hydroxymethylation In Intrauterine Growth Restriction (I...mentioning
confidence: 91%